Isolation, identification and antibiotic sensitivity pattern of aerobic bacteria from burn wound patient admitted in tertiary care hospital - Sah, Amit Kumar; Goel, Varun; Lagamappagol, Siddu (International Journal of Research in Medical Sciences, 2020)
Background: Significant burn injuries induce a state of immunosuppression that predisposes patients to infectious complications, thus the rate of nosocomial infections are higher. Rapidly merging multidrug resistant among the various isolate in indoor burn patients are depending on time-line becoming serious threat for managing therapeutically. Objective of this study is to determine the aetiological factor, prevalence, antimicrobial susceptibility pattern and emerging nosocomial pathogens. Methods: A prospective study was carried in burn ward of K.L.E.’s Dr. Prabhakar Kore Hospital and Medical Research Centre, Belgaum for the period of 1 year. Pair of wound swab were collected from patient having burnt more than 30% (RULE OF NINE) on 3rd day of stay. Sample were collected aseptically from 30 patients and processed by convectional culture and biochemical identification procedures and tested against commonly used antibiotics. Results: 30 patients that fall under inclusive criteria were enrolled in the study. The total burn surface area (TBSA) ranges from 30-82%. The ratio of female to male patient suffering burn wound in our study is 1.5:1. Aetiology of burn is heat (moist/dry) mostly. Depending upon degree of burn, most of patient suffered from 20 degree (superficial to deep) injury. From 30 swab cultures, 42 isolates were identified during the study in which mixed were 66.66% and one is fungi. The most commonly isolated is Pseudomonas aeruginosa (45.24%) then Klebsiella pneumoniae (19.04%), Acinetobacter spp. (14.28%), Staphylococccus aureus (11.90%). Among gram positive isolates, isolates are found to be most resistant to Erythromycin (100%) and Co-trimoxazole (100%) and sensitive to Vancomycin (71.42%). Among gram negative isolates are found to be most resistant to Gentamicin (91.65%), Ciprofloxacin (82.35%), Ceftazidime (82.35%) and sensitive to Meropenem (52.95%), Piperacillin (35.30%), Carbenicillin (29.41%). Conclusions: Pseudomonas aeruginosa was found to be the most common isolate. The nature of microbial wound colonization and flora changes with time should be taken into consideration in empirical antimicrobial therapy.